The Effect of Four Pillars of Education on Self-Efficacy in Type 2 Diabetes Melitus Patients at Royal Prima Hospital Medan - Lawolo, Selpian Putri; Manalu, Paquita Cindriayu; Sitopu, Robin Ferdiansyah; Ardila, Devi (Universitas Malahayati, 2023)
ABSTRACT Diabetes mellitus is a group of metabolic diseases with characteristics of hyperglycemia which occurs due to impaired function of insulin. Education is an outcome that can be carried out for patients in order to increase understanding regarding their health condition so that patients can carry out the self-efficacy needed by patients in the context of success. Implementation of the management of the four pillars of type 2 DM. The purpose of this research is to understand the impact of four pillars of education on type 2 DM patients on self-efficacy. This research uses a quantitative quasi-experimental research approach pre-post test with control by utilizing the two group pre-test and post-test research models carried out with a total sample of 30 informants with 15 intervention informants and then 15 control informants. Techniques in collecting samples using purposive sampling technique. The method used in statistical testing is with the help of the Wilcoxom Signed - Rank Test and the Man Witney Test. This research gives the result that there is an effect of four pillars education on type 2 DM patients with self-efficacy at Royal Prima Medan Hospital. In the Wilcoxom test results obtained in the treatment group p = 0.01 (p <0.05) then the control group obtained the result that there was no effect of four pillars education in type 2 DM patients on self-efficacy p = 0.615 (p> 0.05). The conclusions obtained from the results of this research are that there is an influence of the four pillars of education on self-efficacy in type 2 DM patients at Royal Prima Medan Hospital. Keywords: Diabetes Mellitus, Four Pillars, Self Efficacy ABSTRAK Diabetes melitus merupakan salah satu golongan penyakit metobolik dengan karakteristik pada hiperglikemi yang sangat terjadi karena terjadinya gangguan fungsi pada insulin, Edukasi ialah hasil yang bisa dilakukan pada pasien dalam rangka menambah pemahaman terkait keadaan kesehatannya sehingga pasien dapat melakukan efikasi diri yang dibutuhkan oleh pasien dalam rangka suksesnya pelaksanaan manajemen empat pilar DM tipe 2. Makud dari riset ini ialah untuk memahami dampak edukasi empat pilar pada pasien DM tipe 2 atas efikasi diri. Riset ini menggunakan pendekatan riset kuantitaif quansi experinmental pre-post test with control dengan memanfaatkan metode two group pre test and post test model riset yang dilaksanakan dengan total sampel 30 informan dengan 15 informan intervensi kemudian 15 informan kontrol. Teknik dalam mengumpulkan sampel memanfaatkan teknik purposive sampling. Metode yang dilaksanakan pada pengujian statistik ialah dengan bantuan uji Wilcoxom Signed - Rank Test dan Man Witney Test. Riset ini memberikan hasil bahwa adanya pengaruh edukasi empat pilar pada pasien DM tipe 2 dengan self efficacy di RS Royal Prima Medan. Pada hasil pengujian wilcoxom diperoleh pada grup perlakuan p=0.01 (p<0.05) kemudian grup kontrol diperoleh hasil bahwa tidak terdapat pengaruh edukasi empat pilar pada pasien DM tipe 2 atas self effcacy p =0.615 (p> 0.05). Simpulan yang diperoleh dari hasil riset ini ialah Adanya pengaruh edukasi empat pilar atas self efficacy pada pasien DM tipe 2 di RS Royal Prima Medan.Kata Kunci : Diabetes Melitus, Empat Pilar, Self Effcacy